Student's Physics Achievement in Problem-based Learning: A Quantitative Study - Putri Dwi Sundari; Wulan Sari; Hufri; Silvi Yulia Sari (Postgraduate, University of Mataram, 2025)
Low physics learning outcomes are still a problem in physics learning. Teachers need to think about what strategies could improve student learning outcomes. One of the learning models that could be used is the problem-based learning model. This study aims to describe the differences in learning outcomes of students in the application of problem-based learning models compared to the scientific approach at SMA Negeri 3 Padang. The type of research conducted was a quasi-experiment using the Randomized Posttest Only Control Group Design. The research instrument was a learning outcome test in the form of multiple-choice questions. The data analysis technique used is the Lilliefors test, F-test, and t-test with a significance of 0.05. Based on data analysis, it is obtained that the average physics learning outcomes of student in the knowledge aspect of the experimental class is 82, which is better than the control class, 71. Hypothesis testing showed that tcount> ttable is 3.589> 1.667, which means H1 is accepted and H0 is rejected. It can be concluded that the implementation of the problem-based learning model has a significant effect on the physics learning outcomes of students in class X Phase E SMA Negeri 3 Padang.